The Effect of Family-Centered Care on Glycemic Control in Patients with Type 2 Diabetes - Sundari, Sri; Ismail, Suhartini; Solikin, Solikin; Fitrikasari, Alifiati (JURNAL INFO KESEHATAN, 2024)
Effective diabetes self-care is essential for adults managing diabetes. Additionally, implementing family-centered care can significantly enhance home care efficiency.  This study aims to collect and evaluate findings related to family-centered care in diabetic patients. A systematic review was conducted by searching the following electronic databases: PubMed, Scopus, Science Direct, and Google Scholar. The inclusion articles were published in English from 2013 to 2023, Randomized Controlled Trials (RCTs), and published reviews assessing family-centered care for Type 2 Diabetes Mellitus patients. The systematic review was carried out according to the Preferred Reporting Items for Systematic Review and Meta-analyses (PRISMA) flow diagram, relevant studies were identified and assessed based on the Joanna Briggs Institute (JBI) criteria. These results were discussed among researchers to resolve differences and reach a conclusion. Results: Five RCT reviews published between 2013 and 2023 met the inclusion criteria. Family-centered care can reduce HbA1c levels, blood pressure, weight, depressive symptoms score (PHQ8), and Low-Density Lipoprotein levels, increasing knowledge, self-efficacy, and self-management behaviors. This review has provided evidence regarding the effect of implementing family-centered care interventions in patients with type 2 diabetes mellitus. The evidence suggests that family-centred care can be an important approach to improving the quality of healthcare services for patients with type 2 diabetes mellitus.